Analisis Work Life Balance, Internal Branding Empolyee dan Budaya Organisasi Terhadap Organizational Citizenship Behavior - Muhammad Kosim; Dian Rachmawati Afandi; Pupung Purnamasari; Fiqih Maria Rabiatul Hariroh (Moneter : Jurnal Ekonomi dan Keuangan, 2024)
This study aims to evaluate the impact of Work-Life Balance, Employee Internal Marketing, and Corporate Culture on Organizational Citizenship Behavior (OCB) among employees of PT XYZ Cikarang. OCB is a voluntary action taken by employees to improve organizational performance beyond their official responsibilities. An optimal work-life balance can improve employee well-being and strengthen their commitment to the company. Internal Employee Branding serves to strengthen employees' identity and relationship with the company, while Corporate Culture forms values and norms that encourage constructive behavior in the work environment. This study applies a quantitative method with a multiple regression analysis approach. Information was obtained through questionnaires distributed to employees of PT XYZ Cikarang. The research findings indicate that work-life balance, internal marketing for employees, and organizational culture have a positive and significant impact on OCB, both separately and together. The main factor that is most influential in strengthening OCB is Organizational Culture, which shows the important role of company values and norms in shaping employee attitudes. The findings suggest that companies should improve work-life balance, strengthen internal brands, and create a supportive organizational culture to encourage employees to perform behaviors that go beyond their responsibilities.